2019
DOI: 10.1021/acssuschemeng.9b04141
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Thermochemical Single-Step Process To Obtain Magnetic Activated Carbons from Chestnut Industrial Wastes

Abstract: A novel thermochemical process based on a single step was optimized to obtain magnetic activated carbons from an industrial biomass waste. Anhydrous iron chloride was used as an activating agent and mixed directly with the chestnut shell waste. The effect of the activation temperature (220–800 °C) on the chemical, morphological, textural, and magnetic properties of the materials was studied. The results demonstrated the presence of different iron compounds depending on the activation temperature set as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 90 publications
1
14
3
Order By: Relevance
“…The increase of the activation temperature produced activated carbons with more developed porosity. In this sense, Rodríguez-Sánchez et al [69] observed an increase of the total surface area with activation temperatures in the range of 220 to 800 • C when activating chestnut industrial wastes. However, the use of very high activation temperatures resulted in a lower porosity, as indicated by the lower amount of N 2 adsorbed (mainly in the micropore range, P/P o < 0.4) when increasing the activation temperature from 800 up to 1000 • C ( Figure 4B).…”
Section: Porous Texturementioning
confidence: 97%
See 3 more Smart Citations
“…The increase of the activation temperature produced activated carbons with more developed porosity. In this sense, Rodríguez-Sánchez et al [69] observed an increase of the total surface area with activation temperatures in the range of 220 to 800 • C when activating chestnut industrial wastes. However, the use of very high activation temperatures resulted in a lower porosity, as indicated by the lower amount of N 2 adsorbed (mainly in the micropore range, P/P o < 0.4) when increasing the activation temperature from 800 up to 1000 • C ( Figure 4B).…”
Section: Porous Texturementioning
confidence: 97%
“…Fu et al [65] prepared an activated carbon from biomass after washing with a 0.1-M solution of HCl and with a pH PZC of 5.70. The activation of chestnut waste with FeCl 3 at different activation temperatures yielded carbons with surface pH values between 2.3 and 5.2 after washing with distilled water [69]. Our research group synthesized an activated carbon from lignin by FeCl 3 activation using microwave irradiation and a washing step with a 0.1-M aqueous solution of HCl with a pH PZC of 5.0 (results not published).…”
Section: Surface Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…This finding could be explained by the formation of small ZnO nanoparticles on the biochar surface and within the porous structure of the ZBCs. These particles could block the pores and decrease the amount of nitrogen adsorbed, BET surface area, and porosity …”
Section: Resultsmentioning
confidence: 99%